2020
DOI: 10.1158/2159-8290.cd-20-0596
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of PD-1 Blockade on Severity of COVID-19 in Patients with Lung Cancers

Abstract: In 69 patients with lung cancer who developed COVID-19, disease severity and mortality were high, but prior PD-1 blockade was not a risk factor for poor outcomes in this group, suggesting the therapy should be used when indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
262
4
20

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(295 citation statements)
references
References 36 publications
(53 reference statements)
9
262
4
20
Order By: Relevance
“…Among the 13 subjects with COVID-19 diagnosis con rmed by RT-PCR, mortality was 38.5%, higher than previously reported (range 0-36% in previous studies) [13][14][15][16][17][18][19][20][21][22][23][24]. This could be explained by unfavorable characteristics such as higher median age (range 56-68 years in previous studies [13][14][15][16][17][18][19][20][21][22][23],…”
Section: Covid-19 Impact On the Staffmentioning
confidence: 73%
See 2 more Smart Citations
“…Among the 13 subjects with COVID-19 diagnosis con rmed by RT-PCR, mortality was 38.5%, higher than previously reported (range 0-36% in previous studies) [13][14][15][16][17][18][19][20][21][22][23][24]. This could be explained by unfavorable characteristics such as higher median age (range 56-68 years in previous studies [13][14][15][16][17][18][19][20][21][22][23],…”
Section: Covid-19 Impact On the Staffmentioning
confidence: 73%
“…This generated a large body of recommendations, surveys and guidelines [7][8][10][11]. Nevertheless, currently published clinical data are still limited, especially considering subjects on active treatment [12][13][14][15][16][17][18][19].…”
Section: Covid-19 Impact On the Staffmentioning
confidence: 99%
See 1 more Smart Citation
“…24 This has supported the initiation of a clinical trial using nivolumab (NCT04343144) to treat COVID-19 infection. In addition, confounding factors such as smoking status have affected the severity of COVID-19 infection in PD-1 blockade-exposed patients with lung cancer 25 ; this finding has not been seen in patients with gynecologic cancer. Currently, it is unclear whether immunotherapy has a deleterious effect on COVID-19-infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that healing from COVID-19 is associated with LT PD-1 expression normalization. 51 Nivolumab, a PD-1 blocker, was approved for metastatic melanoma at 3 mg/kg given intravenously once every 2 weeks. It is being evaluated for the efficacy and safety in nivolumab in hospitalized COVID-19 patients at 3 mg/kg intravenously and in a pilot study of adult patients with COVID-19 to evaluate the efficacy of anti-PD-1 antibody in relation to viral clearance and its safety at the low dose of 0.3 mg/kg intravenously.…”
Section: Complement System Inhibitorsmentioning
confidence: 99%